2001
DOI: 10.1021/ac001031f
|View full text |Cite
|
Sign up to set email alerts
|

Comparison of Empirical Peak Capacities for High-Efficiency Capillary Chromatographic Techniques

Abstract: Experimental peak capacities for capillary gas chromatography (GC), capillary liquid chromatography (CLC), and capillary electrochromatography (CEC) were compared. To obtain a meaningful comparison, the following constraints were applied. First, the same sample (mixture of alkylbenzenes) was used as a test mixture for all three techniques; second, the same packing material and column diameter were used in CLC and CEC; and third, isothermal conditions were used in GC, while isocratic conditions were used both i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
8
0

Year Published

2002
2002
2013
2013

Publication Types

Select...
6
3

Relationship

1
8

Authors

Journals

citations
Cited by 20 publications
(9 citation statements)
references
References 25 publications
1
8
0
Order By: Relevance
“…In capillary GC using standard wall-coated open-tubular columns, peak capacities typically range between 120 and 250 for a standard GC temperature gradient program of 5-60 min runtime [30]. Full-scan MS detection adds extra and complementary selectivity to the chromatographic separation and furthermore leads to standardized mass spectra, independent of the type of GC-MS instrument manufacturer.…”
Section: Headspace Extraction and Measurement By Gc-msmentioning
confidence: 99%
“…In capillary GC using standard wall-coated open-tubular columns, peak capacities typically range between 120 and 250 for a standard GC temperature gradient program of 5-60 min runtime [30]. Full-scan MS detection adds extra and complementary selectivity to the chromatographic separation and furthermore leads to standardized mass spectra, independent of the type of GC-MS instrument manufacturer.…”
Section: Headspace Extraction and Measurement By Gc-msmentioning
confidence: 99%
“…For a defined resolution of 2, within a time interval between the first and the last peak and an average peak width at halfheight [31], it was found that the GC method had a higher peak capacity (38.7) than the HPLC method (17.0).…”
Section: Robustness Testingmentioning
confidence: 99%
“…An approach to improve laboratory through� put and analyze a large number of analytes in a single run is to use ultraperformance liquid chromatography (UPLC) systems, which employ particle diameters as small as 1.5 µm and oper� ating pressures higher than 5000 psi. �owever, despite having several applications in the field of toxicology [164,[176][177][178][179], this technology has scarce application in oral fluid ana lysis [180].…”
Section: Lc-msmentioning
confidence: 99%